Ultrasensitive multispecies spectroscopic breath analysis for real-time health monitoring and diagnostics - Liang, Qizhong; Chan, Ya-Chu; Changala, P Bryan; Nesbitt, David J; Ye, Jun; Toscano, Jutta (Proceedings of the National Academy of Sciences - PNAS, 2021)
Breath analysis enables rapid, noninvasive diagnostics, as well as long-term monitoring of human health, through the identification and quantification of exhaled biomarkers. Here, we demonstrate the remarkable capabilities of mid-infrared (mid-IR) cavity-enhanced direct-frequency comb spectroscopy (CE-DFCS) applied to breath analysis. We simultaneously detect and monitor as a function of time four breath biomarkers-[Formula: see text]OH, [Formula: see text], [Formula: see text]O, and HDO-as well as illustrate the feasibility of detecting at least six more ([Formula: see text]CO, [Formula: see text], OCS, [Formula: see text], [Formula: see text], and [Formula: see text]) without modifications to the experimental apparatus. We achieve ultrahigh detection sensitivity at the parts-per-trillion level. This is made possible by the combination of the broadband spectral coverage of a frequency comb, the high spectral resolution afforded by the individual comb teeth, and the sensitivity enhancement resulting from a high-finesse cavity. Exploiting recent advances in frequency comb, optical coating, and photodetector technologies, we can access a large variety of biomarkers with strong carbon-hydrogen-bond spectral signatures in the mid-IR.